2020
DOI: 10.1016/j.csbj.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

A metagenome-wide association study of gut microbiome and visceral fat accumulation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 73 publications
1
36
0
Order By: Relevance
“…Few studies have explored the relationships between gut microbiota and visceral fat. Nie et al (2020) found that members of the families Clostridiales and Lachnospiraceae were strongly negatively correlated with obesity parameters such as WC, VFA, TG, LDL, HbA1c, SBP, and DBP. Most of these correlations were negative, which supports the findings of our analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Few studies have explored the relationships between gut microbiota and visceral fat. Nie et al (2020) found that members of the families Clostridiales and Lachnospiraceae were strongly negatively correlated with obesity parameters such as WC, VFA, TG, LDL, HbA1c, SBP, and DBP. Most of these correlations were negative, which supports the findings of our analysis.…”
Section: Discussionmentioning
confidence: 93%
“…These changes resulted from an increase in SCFA-producing species, which increased the level of SCFAs and upregulated SCFA-GLP1/PYY-associated sensory mediators. C. citroniae was also enriched in the healthy group compared with the obese cohort (Nie et al, 2020). In addition, C. scindens has been shown to inhibit Clostridium difficile infection by producing secondary bile acids that enhance resistance to C. difficile colonization (Mills et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies underline the connection between visceral fat mass and the gut microbiota 6 , 7 . We show here for the first time the link between gut microbiota changes and visceral fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified that gut microbiota are an important factor influencing visceral fat mass independently of diet 6 and some specific microbial metabolic pathways are associated with visceral fat 7 .This may explain the contrasting findings about the links between dietary macronutrient intake and visceral fat mass. For example, while Le Roy et al reported that increasing dietary protein intake is associated with higher visceral fat mass 6 , others have reported the opposite 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the microbial ecology of colonic acetate-and succinate-producing bacteria, especially the Coprococcus_2 and Prevotella groups, may help to explain the influence of diet on the acetate and succinate supply and may contribute to the development of new approaches for optimizing microbial activity for diet management for GDM subjects. Eubacterium ventriosum, another SCFAs producer, had been found negative correlated with visceral fat area (VFA) (39). Moraes et al reported that the abundance of E. ventriosum were associated to better cardiometabolic profile (40).…”
Section: Discussionmentioning
confidence: 99%